Pattern of esophageal cancer in tertiary care hospital in North India: a clinicopathological study - Gupta, Vishal; Bhardwaj, Subash; Bhagat, Opinder Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Esophageal cancer is one of the deadliest and eighth most common cancer worldwide. It is the sixth most common cause of cancer related deaths with developing nations making up more than 80% of total cases and deaths. The purpose of this study was to assess the histopathological pattern of esophageal cancer in our region. Methods: In our centre, we analyzed 101 cases of endoscopic esophageal biopsy proven cases of esophageal cancer from January 2014 to June 2016. In most of these cases, dysphagia was the commonest indication of esophageal endoscopy. Results: 65 cases (64.4%) were males and 36 cases (35.6%) were females. Most of the patients were in the age group of 41-60 years. The histopathological analysis revealed squamous cell carcinoma as the most common esophageal cancer (n=61, 60.4%) followed by adenocarcinoma (n=38, 37.6%) and 02 cases of undifferentiated carcinoma (2%). Conclusions: Esophageal cancer is one of the commonest digestive tract malignancy in India. The males are affected more than the females with male to female ratio of 1.8:1. The maximum number of cases being seen in fifth and sixth decade of life. The squamous cell carcinoma is the most common esophageal cancer seen, with middle esophagus being the commonest site. However, the number of cases of adenocarcinoma are on rise.